Histone deacetylase-dependent transcriptional repression by pRB in yeast occurs independently of interaction through the LXCXE binding cleft - Kennedy, Brian K. (The National Academy of Sciences, 2001)
We have developed a yeast model system to address transcriptional repression by the retinoblastoma protein (pRB). When fused to the DNA-binding domain of Gal4p (DB-pRB), pRB can repress transcription of reporter genes containing Gal4p binding sites; the histone deacetylase activity encoded by yeast RPD3 is required for DB-pRB repression. Mutation of the LXCXE binding cleft in pRB, a region reported to be required for histone deacetylase recruitment, does not interfere with pRB-mediated repression. From these findings based on yeast experiments, we surmise that the small pocket region of pRB must contain an additional domain that confers histone deacetylase-dependent transcriptional repression. This hypothesis was verified by experiments examining pRB-dependent histone deacetylase association in mammalian cells. In addition to RPD3, repression by pRB in yeast requires MSI1, an ortholog of RbAp48, but not SIN3 or SAP30. By comparing the genetic requirements of DB-pRB repression in yeast to those of other DB-repressor fusions, we can suggest a mechanism by which pRB recruits histone deacetylase activity.